Multiphoton imaging of melanoma 3D models with plasmonic nanocapsules. (1st April 2022) - Zamora-Perez, Paula; Xiao, Can; Sanles-Sobrido, Marcos; Rovira-Esteva, Muriel; Conesa, José Javier; Mulens-Arias, Vladimir; Jaque, Daniel; Rivera-Gil, Pilar
Abstract: We report the synthesis of plasmonic nanocapsules and the cellular responses they induce in 3D melanoma models for their perspective use as a photothermal therapeutic agent. The wall of the nanocapsules is composed of polyelectrolytes. The inner part is functionalized with discrete gold nanoislands. The cavity of the nanocapsules contains a fluorescent payload to show their ability for loading a cargo. The nanocapsules exhibit simultaneous two-photon luminescent, fluorescent properties and X-ray contrasting ability. The average fluorescence lifetime (τ) of the nanocapsules measured with FLIM (0.3 ns) is maintained regardless of the intracellular environment, thus proving their abilities for bioimaging of models such as 3D spheroids with a complex architecture. Their multimodal imaging properties are exploited for the first time to study tumorspheres cellular responses exposed to the nanocapsules. Specifically, we studied cellular uptake, toxicity, intracellular fate, generation of reactive oxygen species, and effect on the levels of hypoxia by using multi-photon and confocal laser scanning microscopy. Because of the high X-ray attenuation and atomic number of the gold nanostructure, we imaged the nanocapsule-cell interactions without processing the sample. We confirmed maintenance of the nanocapsules' geometry in the intracellular milieu with no impairment of the cellular ultrastructure. Furthermore, we observed the lack of cellular toxicity and no alteration in oxygen or reactive oxygen species levels. These results in 3D melanoma models contribute to the development of these nanocapsules for their exploitation in future applications as agents for imaging-guided photothermal therapy. Statement of Significance: The novelty of the work is that our plasmonic nanocapsules are multimodal. They are responsive to X-ray and to multiphoton and single-photon excitation. This allowed us to study their interaction with 2D and 3D cellular structures and specifically to obtain information on tumor cell parameters such as hypoxia, reactive oxygen species, and toxicity. These nanocapsules will be further validated as imaging-guided photothermal probes. Graphical abstract: Image, graphical abstract